Efficiency of maternal health services in East Java Province - Mohammad Wasil; Dyah Wulan Sari; Ahmad Solihin (Trunojoyo University of Madura, 2021)
This study aims to determine the level of efficiency of maternal health services, to explain the factors that cause inefficiency in the districts/cities of the province of East Java. Using data envelopment analysis (DEA). The results showed that the variable return to scale (VRS) test results were better than constant return to scale (CRS), there was a change from relatively inefficient using VRS to efficient regions using VRS. The results of partial regression test AAB affect inefficiency, TPM and TTU do not affect. Meanwhile, simultaneously AAB, TPM and TTU affect the inefficiency of health services. So that it can increase the improvement of AAB access to reduce inefficiency.